Assessment of in-situ weathering of an histic andosol-microcosm to field scale study - Bergur Sigfússon 1978- (2004)
Soil pore water carbon from a Histic Andosol from Western Iceland was studied at three different scales; in the field, in undisturbed outdoor mesocosms and in laboratory repacked microcosms. Pore water was extracted using suction cup lysimeters and hollow-fibre tube Rhizon sampler devices. There were significant differences in all measured variables, dissolved inorganic carbon (DIC), dissolved organic carbon (DOC) and pH values between the scales of the experiment. Concentrations of DIC and pH values varied between sampling devices used. Gaseous constituents of soil solution and pH were more susceptible to changes in scale and difference of sampling devices used. DOC concentrations were significantly different near the surface but differences were diminished below 35 cm depth. Studies considering long term changes in pedogenesis or the role of anthropogenic impacts on the pedosphere require considerable experimental duration though they can be conducted with confidence in leaching experiments with micro- and mesocosms. Nearly twenty percent of the organic carbon bound annually in the soil surface horizon under field conditions was lost by leaching of DOC and decomposition to DIC in disturbed non-vegetated microcosms. This percentage increased to 38 % in undisturbed vegetated mesocosms underlining the importance of surface vegetation on the turnover of carbon in soils. Increased influx of nutrients will increase growth and photosynthesis and subsequent carbon sequestration in surface horizons. Increased influx of nutrients and pollutants, such as fluorine, will further mobilise carbon in deep horizons.